The development of the Venetian iconography of Venus: from Giorgione’s idealism to Titian’s realism - Carvalho, Tânia (Revista do Colóquio, 2021)
This article aims to understand the development and consolidation of the Venetian iconography of Venus from comparisons and analyzes on Giorgione’s Sleeping Venus and Titian’s Venus of Urbino, taking into account: the probable visual and textual sources; a possible influence of the treatises on love; besides the role that Venetian culture, the patrons’ preferencies, and the opinions of critics and theorists of art may have had on the transition from Giorgione’s representation – still idealized, despite the growing naturalism –, to that of Titian’s; a purely material beauty, which defined a new standard of representation and became a reference for artists until the 19th century.